PURCHASE INTENTION ENHANCEMENT MODEL THROUGH PHYSICAL EVIDENCE AND BRAND POSITIONING: THE MODERATING ROLE OF SOCIAL MEDIA ORIENTATION (CASE STUDY OF FAMOUS RESTAURANTS IN GROBOGAN) - Yuni Anggraeni; Dita Prameswari (JMBPreneur: Jurnal Manajemen, Bisnis, dan Kewirausahaan, 2025)
Background: Competition in the culinary business world is getting tighter due to the increasing number of competitors, especially in the Purwodadi area, so companies are required to improve marketing by keeping up with changing times.Purpose: The aim of this research is to find out how to increase Purchase Intention at the famous restaurants in Grobogan through Physical Evidence and Brand Positioning with the Moderating Role of Social Media Orientation.Method: This study uses a quantitative method with a descriptive approach. Data were collected through questionnaires distributed to 130 customers using the accidental sampling method. The data obtained were analyzed using multiple linear regression.Results: The results showed that all hypotheses were accepted. Physical Evidence can Positively and Significantly Increase Purchase Intention, Brand Positioning can Positively and Significantly Increase Purchase Intention, Social Media Orientation can Positively and Significantly Moderate the Relationship between Physical Evidence regarding Purchase Intention, Social Media Orientation can Positively and Significantly Moderate the Relationship between Brand Positioning Regarding Purchase Intention.Conclusion: Social Media Orientation can Positively and Significantly Moderate the Relationship between Physical Evidence and Brand Positioning Regarding Purchase Intention in famous restaurant in Grobogan.Suggestion: This research serves as a foundational study, and future research must be further developed regarding the development of methods and confirming the relationship between variables, especially understanding correctly regarding the moderating variables in the research to be carried out. It is also recommended to add other variables